Climate change 2014 : mitigation of climate change : Working Group III contribution to the Fifth assessment report of the Intergovernmental Panel on Climate Change - Intergovernmental Panel on Climate Change. Working Group III; Edenhofer, Ottmar (Cambridge : Cambridge University Press, 2014)
This latest Fifth Assessment Report of the Intergovernmental Panel on Climate Change (IPCC) will again form the standard reference for all those concerned with climate change and its consequences, including students, researchers and policy makers in environmental science, meteorology, climatology, biology, ecology, atmospheric chemistry and environmental policy.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Climatic changes; Climate change mitigation; Global environmental change; Climatic changes -- Government policy; Climatic changes -- International cooperation